Nitric Oxide-Mediated Tumoricidal Activity of Murine Microglial Cells - Brantley, Emily C (Neoplasia Press Inc., 2010)
Experimental metastases in the brain of mice are infiltrated by microglia, and parabiosis experiments of green fluorescent protein (GFP(+)) and GFP(-) mice revealed that these microglia are derived from circulating monocytes (GFP(+), F4/80(+), and CD68(+)). These findings raised the question as to whether microglia (specialized macrophages) possess tumoricidal activity. C8-B4 murine microglia cells were incubated in vitro in medium (control) or in medium containing both lipopolysaccharide and interferon-γ. Control microglia were not tumoricidal against a number of murine and human tumor cells, whereas lipopolysaccharide/interferon-γ-activated microglia lysed murine and human tumor cells by release of nitric oxide. Parallel experiments with murine peritoneal macrophages produced identical results. Neither activated microglia nor activated macrophages lysed nontumorigenic murine or human cells. Collectively, these data demonstrate that brain metastasis-associated microglia are derived from circulating mononuclear cells and exhibit selective and specific tumoricidal activity.